Ballistic impact resistance of additive manufactured high-strength maraging steel: An experimental study. Issue 4 (December 2021) - Costas, Miguel; Edwards-Mowforth, Maisie; Kristoffersen, Martin; Teixeira-Dias, Filipe; Brøtan, Vegard; Paulsen, Christian O.; Børvik, Tore
Maraging steel is a low carbon steel known for its ultra high-strength after heat treatment. In combination with Additive Manufacturing (AM), the properties of maraging steel indicate potential to enable complex geometries and improved performance-to-weight ratios for ballistic protection. This study investigates the ballistic performance of AM maraging steel monolithic plates and profile panels fabricated by powder bed fusion. The mechanical properties of the maraging steel, both in the as-built state and after heat treatment, were revealed through quasi-static and dynamic tests in three different directions with respect to the build direction. Metallurgical studies were also conducted to investigate the microstructure of the material both before and after testing. The ballistic perforation resistance of the maraging steel samples was disclosed in a ballistic range by firing 7.62 mm APM2 bullets towards the different target configurations. Ballistic limit curves and velocities were obtained, demonstrating that the thickest heat-treated AM maraging steel plate has a particularly good potential for ballistic protection. The hard core of the armour piercing bullet broke in all tests and occasionally shattered during tests with heat-treated targets. However, due to the severe brittleness of the material, the targets showed significant fragmentation in some cases and most significantly for the profile panels.